Development And Characterisation Of Inhaled Andrographolide As An Anti-Cancer Agent - Aljothi, Shankar (2024)
Despite the promising anti-cancer activity of andrographolide against lung cancer, its limited water solubility and low bioavailability pose significant challenges for effective oral administration. To address this issue, the current study focused on the development and comparison of two inhalable preparations of andrographolide for pulmonary drug delivery. Precipitation and spray drying , prepared using precipitation and spray drying techniques, and direct spray drying, produced via direct spray drying of andrographolide solution, exhibited favorable in vitro aerosol performance, storage stability, and dissolution profiles. Morphology and crystalline properties of the preparations were confirmed using scanning electron microscopy (sem) and x-ray diffraction (xrd) analysis, respectively. In vitro aerosol dispersion profile was evaluated using a next-generation impactor (ngi). Precipitation and spray drying consisted of elongated crystals with an average diameter of 1.65 ± 0.34 μm while direct spray drying was made of amorphous spherical particles with an average diameter of 1.43 ± 0.19 μm. Both preparations showed inhalable fractions (particle size < 5 μm) of more than 44% making them suitable for pulmonary drug delivery. The 25% inhibitory concentration (ic25) for precipitation and spray drying was 31.91 μg/ml while direct spray drying demonstrated ic25 of 6.57 μg/ml against lung carcinoma cells (a549). Both preparations were relatively stable in a vacuum condition at 30°c up to 3 months. In conclusion,